THE IMPACT OF PERSONALITY TRAITS AND PERSONAL SUITABILITY ON THE LEVEL OF SATISFACTION AND LOYALTY OF WEST JAKARTA COFFEE SHOP CONSUMERS - Jonathan, Calvin; Rodhiah, Rodhiah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to examine the influence of personality traits and self-congruence on the level of customer satisfaction and loyalty in coffee shops in West Jakarta. Coffee shops provide an interesting context for understanding how personality traits and self-congruity can shape consumer experiences in the cafe environment. The population of this study were coffee shop customers in the western Jakarta area. This study used a sample of 120 respondents. The research method in this study was non-probability sampling using the purposive sampling sample collection technique. Data collection was carried out by distributing questionnaires via Google Forms to a sample of regular coffee shop customers in West Jakarta. The questionnaire questions were designed to measure personality traits, perceived self-congruity with the coffee shop brand, level of satisfaction, and level of customer loyalty. The data were analyzed using SEM (structural equation modeling) through the SmartPLS4 software application. The results showed that personality traits, self-congruity, and satisfaction each have a positive and significant influence. However, personality traits and loyalty have a negative and insignificant effect. The results of this study can provide deep insight into how psychological and social factors affect the level of customer satisfaction and loyalty in West Jakarta coffee shops, and these findings can be used by all coffee shops in providing strategic guidance, improving customer experience, optimizing brand image, and building sustainable consumer loyalty in an increasingly competitive coffee market. Keywords: Personality Traits, Self-Congruity, Customer Satisfaction and Loyalty